We are given the equation of circle (x - 4)² + (y + 3)² = 74 , but let's recall the standard equation of circle i.e (x - h)² + (y - k)² = r², where (h, k) is the centre of the circle and r being the radius ;
So, consider the equation of circle ;
![{:\implies \quad \sf (x-4)^(2)+(y+3)^(2)=74}](https://img.qammunity.org/2023/formulas/mathematics/college/x4qcbiuhignel0asg44brp14k7nykjvmcd.png)
Can be further written as ;
![{:\implies \quad \sf (x-4)^(2)+\{y-(-3)\}^(2)=({√(74)})^(2)}](https://img.qammunity.org/2023/formulas/mathematics/college/s6kjpoo3eqgrho8k2s7asgqb9troog7c82.png)
On comparing this equation with the standard equation of Circle, we will get, centre and radius as follows
- Centre = (4, -3)
- Radius = √74 units